量子力学Ⅰ/調和振動子/メモ のバックアップ(No.1)

更新


量子力学I/調和振動子?

解答:1次元の調和振動子

(1)  &math( \left(-\frac{\hbar^2}{2m}\frac{d^2}{dx^2}+\frac{k}{2}x^2\right)\psi(x)=E\psi(x) );

(3)  &math( &-\frac{d^2}{d\xi^2}\big[X(\xi)e^{-\xi^2/2}\big]+\xi^2H(\xi)e^{-\xi^2/2}-\lambda X(\xi)e^{-\xi^2/2}\\ &=-\frac{d}{d\xi}\big[X'(\xi)e^{-\xi^2/2}-\xi X(\xi)e^{-\xi^2/2}\big]+\xi^2H(\xi)e^{-\xi^2/2}-\lambda X(\xi)e^{-\xi^2/2}\\ &=-X''(\xi)e^{-\xi^2/2}+2\xi X'(\xi)e^{-\xi^2/2}+X(\xi)e^{-\xi^2/2}-\lambda X(\xi)e^{-\xi^2/2}\\ &=0\\ );

両辺を e^{-\xi^2/2}\ne 0 で割れば、

 &math( X''(\xi)=2\xi X'(\xi)+(1-\lambda) X(\xi) );

を得る。

(4)  &math( \sum_{l=0}^\infty l(l-1)c_l\xi^{l-2}=2\xi \sum_{l=0}^\infty l c_l\xi^{l-1}+(1-\lambda) \sum_{l=0}^\infty c_l\xi^l );

より l\ge 0 において、

  (l+2)(l+1)c_{l+2}=(2l+1-\lambda)c_l

  c_{l+2}=\frac{2l+1-\lambda}{(l+2)(l+1)}c_l

(5)

  • n=0 のとき \lambda=1 , H_0(\xi)=1
  • n=1 のとき \lambda=3 , H_1(\xi)=2\xi
  • n=2 のとき \lambda=5 , H_2(\xi)=4(1-2\xi^2)
  • n=3 のとき \lambda=7 , H_3(\xi)=c_1(\xi-\frac{2}{3}\xi^3)
  • n=4 のとき \lambda=8 , H_4(\xi)=c_0(1-4\xi^2+\frac{4}{3}\xi^4)
  • ・・・

Counter: 12473 (from 2010/06/03), today: 15, yesterday: 0